Kemunculan Reksa Dana ESG di Indonesia Analisis Strategis Investor Ritel : The Emergence of ESG Mutual Funds in Indonesia: A Strategic Analysis of Retail Investors - Gary Etwanto; Hendy Endarwan; Aliy Rasyid (OGZ Research & Publishing, 2025)
This study explores the growth potential of Environmental, Social, and Governance (ESG)-based mutual funds in Indonesia, while highlighting their implications for retail investors. Building on the findings of Sweta and Yadav (2025) in India, the research applies the PESTEL and SWOT frameworks to capture the local dynamics. The analysis reveals a regulatory paradox: on the one hand, the Financial Services Authority (OJK) promotes sustainable finance through its roadmap and taxonomy; on the other hand, government deregulatory measures such as the Omnibus Law tend to weaken environmental protection. This condition creates an investment landscape that is simultaneously full of opportunities and uncertainties. Key opportunities arise from Indonesia’s young and digitally literate demographics, cultural and religious values aligned with ESG principles, and the rapid growth of the fintech ecosystem. Fintech serves not only as a distribution channel but also as an educational tool, helping to overcome classical barriers such as low financial literacy and perceptions of product complexity. Nevertheless, significant threats remain, including economic volatility that suppresses retail investors’ purchasing power, the risk of greenwashing due to the absence of standardized disclosure, and policy inconsistencies that may undermine the credibility of the ESG market. This article recommends concrete measures to strengthen Indonesia’s sustainable investment ecosystem, including disclosure standardization, digital-based literacy campaigns, and the innovation of hybrid Shariah–ESG products. The synergy among regulators, asset managers, and fintech platforms is essential for building an ESG mutual fund market that is transparent, resilient, and trusted by investors. With these strategies, Indonesia has the potential to become one of the leading hubs of sustainable finance in Southeast Asia.** Purpose: To analyze the strategies and prospects of the emergence of ESG mutual funds in Indonesia, with a focus on retail investors. Methodology: This study employs a qualitative approach through literature analysis, regulatory review, and the application of PESTEL and SWOT frameworks. Findings: The analysis identifies a paradox between OJK’s regulatory support and the government’s deregulatory environmental policies. Opportunities arise from young digital-savvy demographics, fintech as a distribution and education channel, and synergies with Islamic finance. Key barriers include low financial literacy, greenwashing risks, and policy inconsistencies. Keywords: ESG Mutual Funds, Sustainable Finance, Retail Investors, PESTEL, SWOT, OJK, Fintech.